Educational Aspirations and Postsecondary Access and Choice - Hu, Shouping (Education Policy Analysis Archives, 2003)
Using data from the National Education Longitudinal Study of 1988 (NELS: 88), this study examines educational aspirations and postsecondary access and choice by students in urban, suburban, and rural schools. In addition, this study raises issues with the methods in postsecondary educational research by using students in different grades (8th, 10th, and 12th grades) as baseline populations to compare educational outcomes. The results indicated that students in urban schools were comparatively disadvantaged in the early years in schooling in terms of postsecondary access but appeared to be enrolled in postsecondary institutions at similar percentages as their suburban counterparts, if they made it to later years in K-12 schooling. For those students in urban schools who went to college, higher percentages were enrolled in private institutions and four-year colleges. Students in rural schools were consistently disadvantaged in postsecondary aspirations and enrollment, compared to students in other schools.